Characterization of coronary arteries in Giant Anteater (Myrmecophaga tridactyla: Myrmecophagidae) - Cruvinel, C. A. T.; Cruvinel, T. M. A.; Aires, L. P. N.; Rodrigues, R. F. [UNESP]; Melo, A. P. F. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
Were used twelve (12) adult anteaters (Myrmecophaga tridactyla), adults, 6 (six) males and 6 (six) females, weighing from 20 to 27.32kg from free life. The thoracic cavity was opened until visualization of the whole heart and lungs and later injection of the coronary vessels. The right coronary artery emerged through a single coronary ostium of the aorta, 50%, emitting the intermediate branch and the subsinuous interventricular branch, had a path directed to the subsurface interventricular groove. In the other 50%, the right coronary artery was not present, showing only its branches, intermediate branch and subsurface interventricular branch with emergence of the aorta. Left coronary artery presented, in 83.33%, origin from the aorta in single ostium, issuing the circumflex and interventricular paraconal branches. In 16.66%, the left coronary artery was not evidenced originating from the aorta, but its branches, circumflex and interventricular paraconal.
Keywords: heart; coronary artery; wild animals; giant anteaters